Emergence of pandrug-resistant carbapenemase-producing Enterobacterales in dogs and cats: a cross-sectional study in Egypt - Tartor, Yasmine H.; Ammar, Ahmed M.; Abdelkhalek, Adel; Hassan, Khlood A.; Shaker, Asmaa; Elnahriry, Shimaa S.; Nekouei, Omid; Elsohaby, Ibrahim (Frontiers in Cellular and Infection Microbiology, 2024)
One of the most important emerging health problems is the increasing role of animals in the rapid global rise in resistance to last-resort antibiotics, such as carbapenems. However, there is limited information on the role of pet animals in harboring and spreading pandrug-resistant (PDR) carbapenemase-producing Enterobacterales (CPE), especially in Egypt. This cross-sectional study was conducted to screen for CPE in healthy and diseased pets using phenotypic and molecular methods and the NG-Test CARBA 5 immunochromatographic assay. Rectal swabs were collected from 62 dogs and 48 cats, incubated overnight in tryptic soy broth containing 10 μg of meropenem disc and subsequently cultured on MacConkey agar supplemented with meropenem (1 mg/L). Sixty-six isolates (60.6%), including 56 Klebsiella pneumoniae, seven Escherichia coli, and three K. oxytoca isolates, were confirmed to be carbapenem-resistant Enterobacterales (CRE) by the disc diffusion method, broth microdilution test, CNPt-direct, and PCR assay targeting carbapenemase genes. Forty-three (65.2%) dogs and 23 (34.8%) cats carried CPE. Of these, 35 (70.0%) were healthy (including 27 dogs and 8 cats) and 31 (52.5%) were diseased (including 16 dogs and 15 cats). blaOXA-181 was the most common gene detected (42/66, 63.6%), followed by blaIMP (40/66, 60.6%), blaOXA−48−like (29/66, 43.9%), blaKPC and blaVIM (20/66, 30.3% each), and blaNDM (17/66, 25.8%). The identified genotypes were blaKPC-2, blaIMP-1, blaVIM-1, blaNDM-1, and blaNDM-5. The CARBA 5 assay showed higher sensitivity and specificity for the detection of NDM, OXA and KPC than that for VIM and IMP genes. Antimicrobial resistance profiles of CRE isolates revealed 20 PDR, 30 extensively drug-resistant (XDR), and 16 multidrug-resistant (MDR) phenotypes. This study provides evidence of colonization with PDR CPE in dogs and cats. To manage the infection or colonization of pets in veterinary clinical settings, extended surveillance systems should be considered, and the use of critical antibiotics should be strictly controlled.